A Randomized Assessment of Online Learning - Alpert, William T.; Couch, Kenneth A.; Harmon, Oskar R. (American Economic Review, 2016)
A microeconomics principles course employing random assignment across three sections with different teaching models is used to explore learning outcomes as measured by a cumulative final exam for students who participate in traditional face-to-face classroom instruction, blended face-to-face and online instruction with reduced instructor contact time, and a purely online instructional format. Evidence indicates learning outcomes were reduced for students in the purely online section relative to those in the face-to-face format by 5 to 10 points on a cumulative final exam. No statistically significant differences in outcomes are observed for students in the blended relative to the face-to-face section.